The king's curse - Gregory, Philippa (New York : Simon & Schuster, 2014)
The story of lady-in-waiting Margaret Pole and her unique view of King Henry VIII's stratospheric rise to power in Tudor England. Regarded as yet another threat to the volatile King Henry VIII's claim to the throne, Margaret Pole, cousin to Elizabeth of York (known as the White Princess) and daughter of George, Duke of Clarence, is married off to a steady and kind Lancaster supporter--Sir Richard Pole. For his loyalty, Sir Richard is entrusted with the governorship of Wales, but Margaret's contented daily life is changed forever with the arrival of Arthur, the young Prince of Wales, and his beautiful bride, Katherine of Aragon.
"A Touchstone Book."
Includes bibliographical references (pages 605-612).
Keywords: Henry -- VIII, -- King of England, -- 1491-1547 -- Fiction; Salisbury, Margaret Pole, -- Countess of, -- 1473-1541 -- Fiction; Ladies-in-waiting -- England -- History -- 16th century -- Fiction; Nobility -- Great Britain -- History -- 16th century -- Fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction; Historical fiction